Comparison of the validity of two methods for assessing body composition in college football players - Carey, D. G.; Serfass, R. C. (The Journal of Strength and Conditioning Research, 1999)
Three methods for assessing body composition—hydrostatic weighing (HW), bottle buoyancy (BB), and anthropometry (A)—were administered to 89 collegiate football linemen and linebackers. Anthropometry consisted of 2 previously developed, sport-specific equations and 1 generalized equation. The primary purpose of this study was to assess and compare the validity of BB and A. Using HW as the criterion test, repeated measures analysis of variance revealed that the Wickkiser-Kelly equation (WK) (t = 47.44; p < 0.001), the equation of White and colleagues (W) (t = 189.76; p < 0.001) and the Jackson-Pollock equation (JP) (t = 62.08; p < 0.001), all were significantly different from HW and from each other. There was no significant difference between HW and BB (t = 0.12; p = 0.9874). Means (M), standard deviations (SD), correlation coefficients, standard errors of estimate (SEE), and total errors (TE) were as follows: HW (M = 18.3%, SD = 6.5%); WK (M = 21.5%, SD = 7.9%, R = 0.781, SEE = 3.2%, TE 4.9%); W (M = 11.9%, SD = 3.9%, R = 0.779, SEE = 4.3%, TE = 5.7%); JP (M = 14.6%, SD = 5.3%, R = 0.752, SEE = 4.3%, TE = 8.0%). Based on the results of this study, it is concluded that (a) 2 sport-specific and 1 generalized regression equation were not validated, and (b) BB is a valid method for assessing body composition in this group of subjects.